Hubungan gaya asuhan ibu bapa terhadap gejala ponteng sekolah menengah atas di bandar Malang Indonesia - Wulandari, Diana (2018)
In 2014 to 2015, truancy case in Malang City are increase. Eventhough all school programs to reduce truancy have been implemented, including parental counseling in educating children. The purpose of this study to identify the most dominant and significant relationship of parenting styles against the symptoms of truancy, as well as significant differences in terms of relieving parents of students involved with conduct truancy based on gender. Cross sectional survey methods were applied in the data collection process. An instrument used a set of questionnaire Parental Authority Question. The respondent of 500 students with state and private never truancy a minimum of one times during one semester at five district in the city of Malang namely Sukun, Blimbing, Kedungkandang, Klojen and Lowokwaru. The sampling size used purposive sampling method. Descriptive statistics used frequency, percentages, mean and standard deviation is used to analyze the gender, level of truancy, age, and occupation of parents. The inferential statistics – rank-spearman correlation used to analyze parenting styles of the most dominant and significant symptoms of truancy. Chi-square is used to analyze the differences symptoms of truancy between male and female student. Results showed, all parenting styles have a positif and significant relationship on the symptoms of truancy. The style of permissive parents is the most closely related and significant variable to the truancy. There were no significant differences in truancy among boys and girls. In conclusion, based on the findings of the study, it is proposed that continuous monitoring and control be provided to strengthen the understanding of teachers, parents and students to reduce truancy as desired by the Ministry of Education of Indonesia.